Physics Education Students' Views about Force Diagrams while Solving Physics Problems - Sirait, Judyanto; Oktavianty, Erwina; Silitonga, Haratua Tiur Maria; Ainley , Janet (Jurnal Pendidikan IPA Indonesia, 2025)
Force is one of the most fundamental concepts in physics, used to describe and explain a wide range of phenomena. Students can use force diagrams to learn about fundamental force concepts and solve problems related to forces. However, a limited study has focused on students’ views in drawing force diagrams. This study aims to explore students’ views about force diagrams while solving physics problems. A qualitative study was conducted to explore students’ views on drawing and using force diagrams when solving force problems, involving 18 physics education students. Before the semi-structured interviews were conducted, the students were given two force problems to solve. All interviews were recorded, transcribed, and coded for analysis. Data from the interview was analyzed using NVivo software. This study identified five themes related to students’ views on force diagrams: purposes, conventions, physics concepts, mathematical concepts, and incomplete diagrams. The most frequently mentioned theme by students was the purpose of drawing force diagrams. Students’ knowledge about force concepts and trigonometry also affected their diagrams. Students had different ways to draw diagrams, either on the dot or on the object, and had reasons for drawing the incomplete force diagrams. These findings suggest that students should possess sufficient knowledge of physics and mathematics to draw force diagrams effectively. Students should also understand when force diagrams are applicable and recognize the advantages of drawing them. This study suggests that to support students' effective understanding of force diagrams, educators should employ appropriate strategies and equip students with the skills to create and utilize force diagrams while learning about force concepts and solving problems.